A novel risk score model based on gamma-aminobutyric acid signature predicts the survival prognosis of patients with breast cancer - Yang, Liping; Zhu, Jin; Wang, Lieliang; He, Longbo; Gong, Yi; Luo, Qingfeng (Frontiers in Oncology, 2023)
Background: Gamma-aminobutyric acid (GABA) participates in the migration, differentiation, and proliferation of tumor cells. However, the GABA-related risk signature has never been investigated. Hence, we aimed to develop a reliable gene signature based on GABA pathways-related genes (GRGs) to predict the prognosis of breast cancer patients. Methods: GABA-related gene sets were acquired from the MSigDB database, while mRNA gene expression profiles and corresponding clinicopathological data of breast cancer patients were downloaded from GEO and TCGA databases. Univariate Cox regression analysis was used to identify prognostic-associated GRGs. Subsequently, LASSO analysis was applied to establish a risk score model. We also constructed a clinical nomogram to perform a prognosis evaluation. Besides, ESTIMATE and ssGSEA algorithms were used to assess the immune cell infiltration among the risk score subgroups. Results: A GRGs-related risk score model was constructed in the TCGA cohort, and validated in the GSE21653 cohort. The risk score was significantly related to the overall survival of breast cancer patients, which could predict the prognosis of breast cancer patients independently of other clinical features. Breast cancer patients in the low-risk score group exhibited higher immune cell infiltration levels. Conclusion: A novel prognostic model containing five GRGs could accurately predict the prognosis and immune infiltration of breast cancer patients. Our findings provided a novel insight into investigating the immunoregulation roles of GRGs.